MOTIVASI SINGAPURA DALAM MENJADIKAN BOTANIC GARDEN SEBAGAI SITUS WARISAN DUNIA - Hanisa "; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study explains the motivation of Singapore in making the Botanic Garden a World Heritage site. There are many tourist sites that are had by the state of Singapore, namely the Singapore Botanic Garden which has been appointed by UNESCO as one of the world Heritage sites. The Singapore Botanic Garden was inaugurated in July 2015 because it meets the criteria and requirements of UNESCO to be registered as a World Heritage site.This study used the Neorealis perspective in international relations and state-of-the-nation analysis level supported by foreign policy theory This study used the concept of national interests. This research is a qualitative study with the method of deductive analysis. The research scope is the motivation of Singapore in making the Botanic Garden a World Heritage site.The study stated that motivation Singapore in making the Botanic Garden as a World Heritage site is because the Singapore Botanic Garden has the first value of history, aesthetic value, and the Singapore Botanic Garden as a research place and Conservation. The efforts made by Singapore Botanic Garden to enter the UNESCO World Heritage Site began from 2011 to 2015.Keywords: Singapore, Singapore Botanic Garden, UNESCO, World Heritage Site.